INTERACTIVE INSIGHTS: HOW KAHOOT! TRANSFORMS FORMATIVE ASSESSMENT AND ELEVATES PROSPECTIVE TEACHERS’ SUCCESS - Arfa Javed; Dr. Ghazala Noureen (International Journal of Contemporary Issues in Social Sciences, 2024)
This study explores the transformative effect of Kahoot!, a game-based learning platform, on formative assessment practices and academic achievement among prospective teachers. Formative assessment, an essential process in education, fosters continuous learning by providing timely feedback to students and guiding instructional adjustments. Traditional formative assessments often rely on paper-pencil methods, but technological advancements like Kahoot! offer innovative, interactive alternatives that engage students and enhance learning outcomes. This quasi-experimental study was conducted with 60 prospective teachers from a women’s university, divided into experimental and control groups. Students in the experimental group participated in Kahoot! games during class, which served as a formative assessment tool, while the control group followed conventional assessment methods. The study employed a posttest-only control design to compare academic achievement between the two groups. To analyze the data, independent sample t-test was used. The results showed that there was a significant improvement in the academic performance of the experimental group. It also identified the effectiveness of Kahoot! in better student engagement and learning outcomes. The results emphasize Kahoot!’s potential as a dynamic tool for formative assessment, providing real-time feedback, promoting competition, and improving academic success among prospective teachers. The study found that Using Kahoot! resulted in a significant difference in academic achievement between the experimental and control groups.